Influence of isovalent doping on the cathodoluminescence of Li₂B₄O₇:A (A = K, Cu, Ag) single crystals - Adamiv, V.T.; Savchyn, V.P.; Savchyn, P.V.; Teslyuk, I.M.; Burak, Ya.V. (Functional Materials, 2009)
The study results of cathodoluminescence (CL) of isovalently doped Li₂B₄O₇:A single crystals (A = K, Cu, Ag) are reported. The main CL emission mechanism of undoped Ll 2B40 7 is the annihilation of self-trapped excitons (STE). The Cu and Ag impurities have their intrinsic emission bands in CL spectra which are overlaid onto Li₂B₄O₇ STE band about 3.65 eV. The models of CL centers and mechanisms in Li₂B₄O₇:A single crystals are proposed. Представлено результати досліджень катодолюмінесценції (КЛ) ізовалентно заміщених монокристалів Li₂B₄O₇:A (А = К, Cu, Ag). Основним механізмом КЛ свічення нелегованих Li₂B₄O₇ є анігіляція автолокалізованих екситонів (АЛЕ). Домішки Cu і Ag мають свої смуги випромінювання у спектрах КЛ, які накладаються на смугу АЛЕ нелегованого Li₂B₄O₇ біля 3,65 еВ. Запропоновано моделі центрів і механізми КЛ висвічування у монокристалах Li₂B₄O₇:A. Представлены результаты исследований катодолюминесценции (КЛ) изовалентно замещенных монокристаллов Li₂B₄O₇:A (А = К, Cu, Ag). Основным механизмом КЛ свечения нелегированного Li₂B₄O₇ является аннигиляция автолокализированных экситонов (АЛЭ). Примеси Cu и Ag имеют свои полосы излучения в спектрах КЛ, которые накладываются на полосу АЛЭ нелегированного Li₂B₄O₇ около 3,65 эВ. Предложены модели центров и механизмы КЛ свечения в монокристаллах Li₂B₄O₇:A.